History of occupational accidents and near misses and sleepiness in Italian professional drivers: a cross-sectional study - Lucia Palandri; Lucia Palandri; Elena Righi; Elena Righi; Patrizia Melloni; Fabriziomaria Gobba; Federico Ricci; Alberto Modenese; Alberto Modenese (Frontiers in Public Health)
BackgroundSleep difficulties among professional drivers are a major concern for health and safety as they can be associated with increased tiredness while driving and can be related to an increased risk of accidents. Several lifestyle-related risk factors can have an important impact on sleep. This study aims to investigate whether a history of work accidents or near misses is associated with abnormal sleepiness among a sample of Italian professional drivers, considering individual and occupational factors that may influence this relationship.MethodsFrom 2018 to 2022, we conducted a cross-sectional study recruiting professional drivers attending mandatory health and safety training courses in accordance with Italian legislation. Participants completed a six-section questionnaire including personal information, sleep-related difficulties, occupational data, habits, history of accidents and near misses, and the Epworth Sleepiness Scale (ESS). We used multiple logistic regression models to calculate odds ratios (ORs) and 95% confidence intervals (CIs) for abnormal sleepiness.ResultsThe sample comprised 884 workers, predominantly male (99%), with mean age 49.4 years. Our study showed associations between several risk factors and excessive sleepiness. Consuming alcohol showed an increased probability of higher ESS scores. Similarly, snoring and having a history of occupational accidents or near misses showed increased probability of abnormal sleepiness.ConclusionThis study suggests a potential association between a history of near misses and abnormal sleepiness among professional drivers. The observed relationship underscores the need to address underlying sleep disorders, such as undiagnosed sleep apnea, which may contribute to excessive sleepiness and compromised safety. Drivers with a history of work accidents or near misses should be considered for screening programs targeting abnormal sleepiness, as these events may serve as early warning signs. Educational interventions to raise awareness and promote better sleep hygiene among this at-risk group could play a crucial role in improving both occupational health and road safety. Despite limitations inherent to self-reported data, our findings offer valuable insights for targeted prevention strategies.